Effects of dilute HCl on yeast tRNA(Phe) and E. coli tRNA(fMet)(1) - Ladner, Jane E. (1974)
HCl treatment of yeast tRNA(Phe) under conditions generally used for excision of `Y' base results in structure and conformation changes as monitored by line widths in the PMR spectra at 220 MHz and by optical rotation. Like exposure of E. coli tRNA(fMet)(1) causes similar changes in the PMR spectra and optical rotation although no residues are eliminated. Electrophoresis in polyacrylamide gels provides evidence for aggregation in HCl-treated tRNA(fMet)(1). One must thus consider a general effect of HCl exposure as well as possible residue removal in assessing induced structural and conformation changes in tRNA.